The Edinburgh companion to romanticism and the arts - McCue, Maureen; Thomas, Sophie (Edinburgh University Press, 2023)
"From the birth of the museum to the explosion of mass-produced illustrated books, the Romantic period (c. 1770-1840) was a moment of rapid change and fruitful experimentation in the fields of art and literature alike. New advances in print production encouraged a wider range of readers to engage with literary forms that opened a path into the once aristocratic field of the visual arts. This Companion captures the way recent engagements with visual studies have reshaped how we approach and understand the boundaries between print and visual culture in the period. It brings together 27 research-led chapters that offer a detailed account of the productive, if sometimes tense, interactions between emergent forms of intermedial expression that were redefining culture in the Romantic period -- as they continue to do today" -- $$c Provided by publisher.
Keywords: Romanticism in art.; Romanticism.; Arts, Modern -- 18th century.; Art and literature.; Romantisme dans l'art.; Romantisme.; Arts -- 18e siècle.; Art et littérature.; romanticism (form of expression); Romanticism in art; Arts, Modern; Art and literature; Romanticism; Literature: history & criticism.; Literary studies: fiction, novelists & prose writers.; Literary companions, book reviews & guides.; Literature.; 1700-1799; 1700-1899; Electronic book.